Zoonotic Enterocytozoon bieneusi genotypes in free-ranging and farmed wild ungulates in Spain. (12th September 2022) - Dashti, Alejandro; Santín, Mónica; Köster, Pamela C; Bailo, Begoña; Ortega, Sheila; Imaña, Elena; Habela, Miguel Ángel; Rivero-Juarez, Antonio; Vicente, Joaquin; ,; Arnal, Maria C; de Luco, Daniel Fernández; et al.
Abstract: Microsporidia comprises a diverse group of obligate, intracellular, and spore-forming parasites that infect a wide range of animals. Among them, Enterocytozoon bieneusi is the most frequently reported species in humans and other mammals and birds. Data on the epidemiology of E. bieneusi in wildlife are limited. Hence, E. bieneusi was investigated in eight wild ungulate species present in Spain (genera Ammotragus, Capra, Capreolus, Cervus, Dama, Ovis, Rupicapra, and Sus ) by molecular methods. Faecal samples were collected from free-ranging ( n = 1058) and farmed ( n = 324) wild ungulates from five Spanish bioregions. The parasite was detected only in red deer (10.4%, 68/653) and wild boar (0.8%, 3/359). Enterocytozoon bieneusi infections were more common in farmed (19.4%, 63/324) than in wild (1.5%, 5/329) red deer. A total of 11 genotypes were identified in red deer, eight known (BEB6, BEB17, EbCar2, HLJD-V, MWC_d1, S5, Type IV, and Wildboar3) and three novel (DeerSpEb1, DeerSpEb2, and DeerSpEb3) genotypes. Mixed genotype infections were detected in 15.9% of farmed red deer. Two genotypes were identified in wild boar, a known (Wildboar3) and a novel (WildboarSpEb1) genotypes. All genotypes identified belonged to E. bieneusi zoonotic Groups 1 and 2. This study provides the most comprehensive epidemiological study of E. bieneusi in Spanish ungulates to date, representing the first evidence of the parasite in wild red deer populations worldwide. Spanish wild boars and red deer are reservoir of zoonotic genotypes of E. bieneusi and might play an underestimated role in the transmission of this microsporidian species to humans and other animals. Lay Summary: The fungal-related intracellular parasite Enterocytozoon bieneusi is a worldwide public health and veterinary problem. Here we demonstrated that it was present in wild boar, and wild and farmed red deer in Spain, with genotypes potentially capable of infecting humans, posing a public health risk.